2021
DOI: 10.5812/zjrms.98400
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Death Anxiety Among Hemodialysis Patients

Abstract: Background: Hemodialysis improves renal function and increases lifetime. However, it causes a fundamental change in the whole life of patients. Many of these patients express their fears of an unacceptable life. Objectives: This study aimed to evaluate the quality of life and death anxiety among patients on hemodialysis and determine their personality and demographic predictors. Methods: A total of 154 participants were recruited from the hemodialysis units of hospitals in Zahedan, the southeast of Iran. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Also, anxiety together with other psychological constructs like depression have been linked to poor and/or lower QoL among patients with heart failure [65][66][67][68]. Death anxiety was present among a greater number of hemodialysis patients while they recorded low to moderate QoL, and among the domains of QoL, psychological and physical domains had the worst reductions [69]. Furthermore, anxiety was found to be negatively associated with the psychological, environmental, and social relationships domains of QoL [70].…”
Section: Discussionmentioning
confidence: 99%
“…Also, anxiety together with other psychological constructs like depression have been linked to poor and/or lower QoL among patients with heart failure [65][66][67][68]. Death anxiety was present among a greater number of hemodialysis patients while they recorded low to moderate QoL, and among the domains of QoL, psychological and physical domains had the worst reductions [69]. Furthermore, anxiety was found to be negatively associated with the psychological, environmental, and social relationships domains of QoL [70].…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-four percent of participants in an ESDR trial exhibited high levels of death anxiety. Approximately 70% of the patients had a low or moderate quality of life ( Ghiasi et al, 2021 ). According to the findings, it is vital to address the death anxiety of ESDR patients receiving hemodialysis ( Dewina et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This progress in prognosis leads to a decrease in the patient’s hope for recovery and may also cause a stronger feeling of death. Previous studies showed that hope is low, hopelessness is high, and death anxiety is serious in kidney patients (Cengiz & Saritas, 2019; Dewina et al, 2018; Ercan & Demir, 2018; Ghiasi et al, 2021; Soylu & Tuna, 2019). A kidney transplant is the only way for patients to recover from life-long renal failure and the dialysis treatment they are dependent on.…”
Section: Introductionmentioning
confidence: 99%
“…All these situations and long waiting periods lead patients to feel that they are approaching death instead of being able to recover and regain their health. In particular, the number of studies reporting that patients with ESRF receiving dialysis treatment have decreased hope of recovery, see death as salvation, and do not have any expectations that they can have a kidney transplant is increasing (Burns et al, 2017; Dewina et al, 2018; Ghiasi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%